THEORETICAL AND METHODOLOGICAL ASPECTS OF AN ENTERPRISE STRATEGIC ACCOUNTING SYSTEM FORMATION - RUDENKO, Serhii; OREL, Volodymyr; LAGODIIENKO, Nataliia; BIRCHENKO, Nataliia; MOROZ, Anton (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article reveals the theoretical and methodological principles of strategic accounting system development at the enterprise as the basis for the formation of information support for strategic management. The essence, functions, and principles of strategic accounting are determined, and its differences from the traditional accounting system are presented. It is emphasized that strategic accounting is oriented towards the future and the development of activities and should integrate financial and non-financial indicators, as well as internal and external information, necessary for making strategic decisions. The conceptual model of strategic accounting is proposed based on the principles of systematicity, adaptability, relevance, continuity, integration, and purposefulness.Particular attention is paid to the methodical tools of strategic accounting: Activity-Based Costing, target costing, value chain analysis, life cycle costing, balanced scorecard, and benchmarking. For each of them, the advantages and disadvantages of the application are identified, and the effects of their implementation are indicated. The comprehensive application of these methods will ensure the formation of information support for the strategic management process. However, for an optimal and relevant choice, it is necessary to rely on the functional features of the methods, as well as their advantages and disadvantages in application.An approach to creating a chart of strategic accounts is proposed, which involves introducing specialized accounts to reflect strategic investments, costs, intangible assets, and reserves. Such detailing provides a comprehensive reflection of the strategically important elements of the enterprise's activities that underpin the company's competitive advantages and long-term value.The results of the study have practical importance for improving the accounting system and analytical support for strategic management, increasing the efficiency of planning, control, and assessment of the implementation of the enterprise's strategy. The implementation of the proposed approach will contribute to strengthening competitiveness, ensuring sustainable development, and the strategic development of enterprises amid dynamic changes in the external environment.
Keywords: strategic accounting; management accounting; strategic management; accounting policy; cost accounting; assets; chart of accounts